(untitled) (Revista de Ciências Agroveterinárias, 2024)
This study details the distribution of solid-colored alpacas in relation to their breed, gender, and age in the community of San Miguel de Mestizas, Apurímac. A total of 244 Suri genotype and 2,256 Huacaya alpacas were evaluated. Fleece color determination was carried out through observation and recorded on a registration form. A significant disparity in the proportion of solid-colored alpacas was found between Suri (10.8%) and Huacaya (89.2%) breeds, even after expanding the analysis to include all alpacas. The low prevalence of Suri was attributed to its increased vulnerability in Andean environments, reflected in higher mortality rates and lower reproduction. The study highlighted a predominance of female alpacas (69.6%), indicating management practices focused on males, impacting birth rates and offspring survival. Age-specific analysis revealed challenges in reproduction, with a limited proportion of alpacas in the milk teeth stage. In Huacaya, a preference for white fleece (66.8%) was evident, indicating a growing demand for colored fleeces. Suri alpacas showed a high proportion of females (71.2%) and a preference for solid colors, but the decline in solid-colored Suri raises concerns about genetic diversity. This detailed analysis emphasizes challenges in population management, color preferences, and the need to preserve genetic variability in the face of the growing demand for colored fleeces in San Miguel de Mestizas.